Effect of crude palm oil (CPO) as an additive in the asphalt mixture - Wan Abdullah, Wan Zakkhry (2017)
There are various types of method used to produce Hot Mix Asphalt (HMA) for the road pavement such as Marshall Mix Design, Hveem Method and the latest method called Superior Performing Asphalt Pavement or Superpave. There are many problems arise related to healthcare of the workers on paving site and emissions of heat and odor. Emission of heat and odour during placement are dangerous to the public near the construction site and most affected is the construction workers. Moreover, PAH which is Polycyclic Aromatic Hydrocarbon where the most dangerous fumes emission can be found during mixing process of Hot Mix Asphalt (HMA). PAH contains carcinogenic, mutagenic and teratogenic in which can be hazardous to health. Saving energy consumption surely helps in emission of greenhouse gases and conservation of natural resources. This study was conducted to determine the potential of Crude Palm Oil as an additive in asphalt mixture in order to lower the mixing temperature of Hot Mix Asphalt. In addition, this study also focuses on the evaluation of the mechanical properties of the specimens (crude palm oil) in the Marshall Mix Design Method. The flexible road pavement that to be constructed by adding 0.3% of the CPO into hot mix asphalt mixture can be improved in terms of reducing heat and emission of hazardous gaseous without affecting the workability, durability, stability and the strength of the HMA. All of the related tests were conducted in the highway laboratory to collect data and determine the Marshall properties of HMA. All the information which related to procedures, processes and techniques used to produce HMA with additional of CPO will be explained detailed in this study. The information and the guideline used to obtain and calculate all the properties of the material for HMA to ensure the mixture produced will meet the requirement and criteria for the Marshall Mix Design also will be included. As a result, this study was not successfully achieved its main objective which is, either CPO or the temperatures are the causes of the failure in VFA values. For this reason, more research and experimental work needed to be done to evaluate the material performance on the physical and chemical properties of asphalts and the additive (CPO).